PENINGKATAN KUALITAS PELAYANAN TERHADAP KONSUMEN DENGAN MENGGUNAKAN METODE SERVICE QUALITY DAN IMPORTANCE PERFORMANCE ANALYSIS - Gunawan, Akbar; Mutakin, ade irman; Galih, Restu Azi; barleany, dhena ria; khatili, putiri buana (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
This research aims to improve the service quality at Selakosa Coffee using Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. As competition in the coffee shop industry increases, providing excellent service has become crucial to attract and retain customers. The study surveyed 90 respondents and analyzed five key dimensions of service quality: tangibility, reliability, responsiveness, assurance, and empathy. The results revealed significant gaps between customer expectations and actual service in three key areas: indoor space size, toilet availability, and cleanliness. These factors were categorized as high-priority issues based on the IPA Cartesian diagram, indicating that immediate improvements are needed. The root causes of these service shortcomings were analyzed using the fishbone diagram, and improvement recommendations were formulated using the 5W + 1H method. The study concludes that by addressing these gaps, Selakosa Coffee can enhance customer satisfaction, reduce complaints, and strengthen its market position. Future studies could explore additional service variables and include a larger sample size for more comprehensive results